Physical Exercise and Redox Balance in Type 2 Diabetics: Effects of Moderate Training on Biomarkers of Oxidative Stress and DNA Damage Evaluated through Comet Assay. (19th February 2015) - Pittaluga, Monica; Sgadari, Antonio; Dimauro, Ivan; Tavazzi, Barbara; Parisi, Paolo; Caporossi, Daniela
Abstract : Objective. Hyperglycemia leads to increased production of reactive oxygen species (ROS) in type 2 diabetes, which reduces cellular antioxidant defenses and induces DNA lesions. The aim of this study was to investigate the effects on redox homeostasis and DNA oxidative damage of exercise training in patients with type 2 diabetes compared with nondiabetic individuals. Methods and Results. 12 sedentary type 2 diabetic males (62.1 ± 4.3 yrs) and 12 sedentary healthy males (61.7 ± 3.9 yrs) were exposed to 4-month moderate training, 3 times per week, to evaluate the effect on plasma biomarkers of oxidative stress malondialdehyde and antioxidant status (GSSG, GSH/GSSG, and ascorbic acid) as well as basal and H2 O2 -induced DNA damage trough alkaline comet assay in peripheral blood lymphocytes. After training, glutathione and ascorbic acid levels increased in both groups, but only in diabetics the malondialdehyde as well as the DNA damage decreased. Conclusion. Our study demonstrates for the first time that moderate exercise training is not only effective in improving the redox homeostasis, through an increase of the endogenous antioxidant defences in healthy as well as in diabetic patients, but also, specifically in diabetic patients, effective in lowering the susceptibility to oxidative DNA damage and the lipid peroxidation levels.